(untitled) (Global Journal of Management and Business Research, 2023)
The subject of the article is the analysis of the practice of reflecting leasing operations in financial statements The object of the study is the existing system in Azerbaijan of accounting for financial lease agreements between the parties to the lease agreement on accounting accounts At the same time serious attention is paid to the activities of Azerbaijani leasing organizations engaged in financial leasing